Protection of Women Against Rape Crime from The Perspective of Positive Law and Hindu Law - Anak Agung Sagung Laksmi Dewi; I Nyoman Gede Sugiartha (Budapest International Research and Critics University, 2022)
There are many forms of crime that occur on our beloved Earth. The crime of rape is a crime of depriving women of honor and virginity. Although rape crime has been regulated normatively in the Criminal Code, in reality, the protection of rape victims remains inadequate. From the perspective of Hindu Law, committing rape is a great sin. In Sad Atatayi, rape is called Dratikrama. As such, the authors formulated the following research questions to be explored further: How is the regulation of rape delict from the perspective of criminal law and Hindu law? What is the sanction for rape crime in criminal law and Hindu law? This research is normative research. The results of this research are: the regulation of rape delict against women is contained in Article 285-289 of the Criminal Code and in the Hindu Law Compendium (Manawa Dharmasastra). Sanctions for rape against women in criminal law still vary, depending on the provisions that are violated in the Criminal Code and Hindu Law. It depends on the type of crime, whether it is an aggravated crime or an ordinary crime.